Curse of the bane / 2. - Delaney, Joseph, 1945- (Delaney, Joseph, 1945- Last apprentice, 2007)
The Spook and his apprentice, Thomas Ward, have been successful in ridding the county of witches, ghosts, and boggarts, but they face a much more formidable task when they travel to Priestown to confront the Bane and the Quisitor.